Evolution of teacher training courses after implementation of the national higher education assessment system in Baixada Santista - Eduardo de Freitas Santos , Neil; Paula Taboada Sobral, Ana; Leticia Leal Goncalves , Marcela; Maria Altavista Sagretti Gallo, Juliana; Malavasi, Abigail; Candelaria Volponi Moraes de Oliveira, Maria; dos Santos Tavares , Elizabeth; Duarte Mendes , Gustavo; Kalil Bussadori , Sandra; Marcílio Santos, Elaine (Seven Editora, 2023)
The National Higher Education Assessment System (SINAES) created in 2004 has the purpose of improving the quality of higher education, to value public investments and give due return to society. Composed of three basic axes: assessment, regulation, and supervision, SINAES seeks to ensure the integration of internal and external dimensions, the particular and global approach, the somatic and formative aspect, as well as the quantitative and qualitative analysis of the evaluation. The objective of this study was to evaluate teacher training through a comparison between indicators from SINAES, Preliminary Course Concept (CPC) and the National Student Performance Exam (ENADE) to contribute to the improvement of teaching practices in teaching. fundamental, identifying the evolution of these indicators in Baixada Santista. For this, a comparison of the results of the pedagogy courses referring to the ENADE and CPC indicators was carried out based on the information from the Annual Census of Higher Education carried out by the Ministry of Education, highlighting the administrative category, academic organization, and teaching modality. The result points to an increase in pedagogy courses with an unsatisfactory ENADE concept and an increase in courses with a CPC concept of excellence. DOI: 10.56238/pacfdnsv1-014